Writing warfare. Fogwill against Borgean ethics, or the story as a critical operation (Anclajes, 2021)
In this article I propose an approach to Rodolfo Fogwill’s literary policy through an analysis of two critical articles and the stories “Sobre el arte de la novela” (1985) and “Help a él” (1985). Through these texts, we can observe the modulations of a critical operation which takes as reference point the controversy towards Borgean literature and an emerging counter-canon during the 1980s. This operation is an intervention against the literary consensus, and also generates various forms of writing in which fiction hybridizes with theoretical practice. In this sense, Fogwill carried out a desecration of the Argentine literary language, in order to display an exasperated aesthetic dedicated to the meticulous recording of the experiences (bodily, political, cultural) that make up the material world.
Keywords: Fogwill; desecration; Borges; argentine literature; 20th century